Trier, Deutschland. Porta Nigra - Wulf-Rheidt, Ulrike (e-Forschungsberichte des DAI, 2023)
The Porta Nigra in Trier is the best preserved Roman town gate north of the Alps. It belongs to the rare antique large-scale buildings with a long usage and modification history, nonetheless, a major part of its antique substance was preserved. Despite its favorable conservation status and the importance of its architectural history, the Porta Nigra has so far not been satisfactorily studied. Since June 2012 preparations for an extensive basic renovation of this UNESCO World Heritage are conducted by the Rhineland-Palatinate state. This offered for the Division of Building Archaeology at the Head Office of the DAI the opportunity to execute an architectural survey in conformity with current scientific standards. This survey provides a reliable basis for an archaeological and architectural study of the entire complex for the first time.